2023
DOI: 10.3390/sym15101864
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Design Approach for Resonant DC/AC Converters, Based on Symmetry in Their Operating Modes

Nikolay Hinov

Abstract: The manuscript presents an innovative approach for the engineering design of resonant DC/AC converters used as sources of high-frequency electricity for a variety of needs: industrial and domestic applications, wireless power transmission, high-performance lighting, and more. The methodology is based on the generalized consideration of electromagnetic processes in a series resonant RLC circuit fed by a square-wave voltage source. Due to the symmetry in the form of the current in the AC circuit of the DC/AC con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…After the three-phase symmetrical currents pass through the symmetrical three-phase stator winding, a circular rotating magnetic field is generated, which drives the motor to rotate. This concise and elegant symmetrical design reduces system complexity, and improves output performance, which is of great significance [25]. In addition to two-level converters, symmetry is commonly present in power converters, as shown in the four types of three-level inverters in Figure 2, the multi-level cascaded inverters in Figure 3, and the matrix converters in Figure 4.…”
Section: Symmetry-a Common Property Of Power Convertersmentioning
confidence: 99%
“…After the three-phase symmetrical currents pass through the symmetrical three-phase stator winding, a circular rotating magnetic field is generated, which drives the motor to rotate. This concise and elegant symmetrical design reduces system complexity, and improves output performance, which is of great significance [25]. In addition to two-level converters, symmetry is commonly present in power converters, as shown in the four types of three-level inverters in Figure 2, the multi-level cascaded inverters in Figure 3, and the matrix converters in Figure 4.…”
Section: Symmetry-a Common Property Of Power Convertersmentioning
confidence: 99%
“…Currently, converters based on power electronics are ubiquitous components across various sectors, including but not limited to renewable energy sources, the aerospace sector, electric machine drives, the automotive sector, railway systems, and electrical substations [1][2][3][4][5]. The design of power converters, which incorporates both passive elements and control mechanisms, is being continuously refined and adapted for specific uses, a trend supported by numerous publications [3][4][5]. The progression in power electronics technology is being pushed forward with the introduction of power devices crafted by modern semiconductors such as gallium nitride (GaN) and silicon carbide (SiC).…”
Section: Introductionmentioning
confidence: 99%
“…The authors, because of their many years of work in the field of power electronics, have found that for inverter design purposes it is good to use the following inputs: cos(φ T ) -load power factor, from where When designing all types of inverters, at some stage of the design it is necessary to calculate the following basic quantities [5,6]:…”
Section: Introductionmentioning
confidence: 99%